1,5-Bis(4-chlorophenyl)-3-[4-(dimethylamino)phenyl]pentane-1,5-dione (Acta Crystallographica Section E, 2009)
In the title molecule, C25H23Cl2NO2, the central benzene ring forms dihedral angles of 81.88 (7) and 89.22 (7)° with the two 4-chlorophenyl fragments. The crystal packing exhibits weak intermolecular C—H...O hydrogen bonds and π–π interactions [centroid–centroid distance 3.724 (3) Å].